Rapid Progression of Focal Segmental Glomerulosclerosis in Patients with High-Risk APOL1 Genotypes. Issue 3 (8th March 2023) - Kallash, Mahmoud; Wang, Yujie; Smith, Abigail; Trachtman, Howard; Gbadegesin, Rasheed; Nester, Carla; Canetta, Pietro; Wang, Chen; Hunley, Tracy E.; Sperati, C. John; Selewski, David; Ayoub, Isabelle; et al.
Visual Abstract: Abstract : Background: FSGS is a heterogeneous diagnosis with a guarded prognosis. Polymorphisms in the apolipoprotein L1 ( APOL1 ) gene are associated with developing FSGS and faster progression to kidney failure in affected patients. Better understanding the natural history of patients with FSGS and APOL1 risk alleles is essential to improve patient care and support the design and interpretation of interventional studies. The objective of this study was to evaluate the quantitative association between APOL1 and kidney disease progression and the interaction with other clinical and laboratory factors. Methods: CureGN cohort study participants with biopsy diagnosis of FSGS, regardless of self-identified race, were included. The exposure of interest was two APOL1 risk alleles (high risk) versus zero to one risk alleles (low risk). The primary outcome was eGFR slope categorized as rapid progressor (eGFR slope ≤−5 ml/min per year), intermediate progressor (slope between 0 and −5), or nonprogressor (slope ≥0). Multivariable ordinal logistic and linear regressions were used for adjusted analyses. Missing data were addressed using multiple imputation. Results: Of 650 participants, 476 (73%) had genetic testing, among whom 87 (18%) were high risk. High-risk participants were more likely to have lower median eGFR (62 [interquartile range, 36–81] versus low-risk participants 76 ml/min per 1.73 m 2 [interquartile range, 44–106]; P <0.01). In adjusted analysis, the odds of more rapid progression of eGFR was 2.75 times higher (95% confidence interval, 1.67 to 4.53; P <0.001) in the high-risk versus low-risk groups. Conclusions: In patients with FSGS, high-risk APOL1 genotype is the predominant factor associated with more rapid loss of kidney function.